Pengaruh Moralitas Individu dan Pengendalian Internal terhadap Kecurangan: Sebuah Studi Eksperimental - Muhammad Harry Krishna Mulia; Rahmat Febrianto; Rayna Kartika (Journal of Accounting and Investment, 2017)
The purpose of this research was to examine the influence of individual morality and internal control on accounting fraud at students majoring in accounting. The research method in this study is an experimental method using a full factorial experimental design 2x2, involving 108 undergraduate students majoring in accounting Andalas University. The instruments used were mach IV test for individual morality and add to 10 matrices for internal control. Data were processed using SPSS version 21, using two-way ANOVA. The results showed that there was an interaction between individual morality and internal control. Conditions when there is an element of internal control affects people with high moral level to tend to not perform accounting fraud. While individuals with low moral level, there is or there is no internal control individuals tend to do the accounting fraud.